Pengaruh Disiplin Kerja Motivasi Dan Pengembangan Karir Terhadap Kinerja Karyawan (Study Kasus Karyawan KUD Pakis Malang) - Hasbi Alim; M Ridwan Basalamah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study is to know and analyze work discipline, work motivation and career development have an effect simultaneously on the performance of employees of KUD Pakis Malang. To Know the Effect of Work Discipline on Employee Performance of KUD Pakis Malang. To determine the effect of work motivation on the performance of employees of KUD Pakis Malang. To determine the effect of career development on employee performance of KUD Pakis Malang.The population of this study was 33 respondents, and all 33 participants in the sample used experimental methods as the population did not exceed 100 people. Information was then gathered through questioning. Details used SPSS version 16 in this study. Experiments using state-of-the-art and data analysis methods utilize test evidence, test reliability, standard visual analysis, multiline analysis, and test data analysis.The results of the data analysis show that work discipline, motivation and career growth simultaneously affect employee productivity, and in some cases work discipline and career motivation affect the performance of KUD Pakis Malang employees. Keywords: Work Discipline, Work Motivation and Career Development on Employee Performance